2007
DOI: 10.1111/j.1538-7836.2007.02522.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient induction of immune tolerance to coagulation factor IX following direct intramuscular gene transfer

Abstract: , SEM ± 35.7) and hFIX-specific immune tolerance in C57BL/6 mice. Conclusions: A single i.m. of AAV1 can result in efficient expression of therapeutic levels of hFIX and induction of hFIX tolerance in hemostatically normal and hemophilic B mice. Our results substantiate the prospect of i.m. of AAV1 for hemophilia B gene therapy and FIX tolerance induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…As discussed above, the enhanced levels of antigen expression through CTLA4-Ig fusion could be contributing to a high-dose tolerogenic effect. 33,39,40 Alternatively, CTLA4 negatively regulates T-lymphocyte activation through binding with B7 costimulatory molecules, 41,42 and in this manner, CTLA4-Ig has been shown to prevent immunity through B7 blockade 27 and the upregulation of a tryptophancatabolizing pathway for tolerance induction. 32 Surprisingly, tolerance in this study was induced independently of CTLA4-Ig binding with B7 molecules as shown by mutating the MYPPPY-binding motif of the vector construct.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, the enhanced levels of antigen expression through CTLA4-Ig fusion could be contributing to a high-dose tolerogenic effect. 33,39,40 Alternatively, CTLA4 negatively regulates T-lymphocyte activation through binding with B7 costimulatory molecules, 41,42 and in this manner, CTLA4-Ig has been shown to prevent immunity through B7 blockade 27 and the upregulation of a tryptophancatabolizing pathway for tolerance induction. 32 Surprisingly, tolerance in this study was induced independently of CTLA4-Ig binding with B7 molecules as shown by mutating the MYPPPY-binding motif of the vector construct.…”
Section: Discussionmentioning
confidence: 99%
“…28 In small animal models liver-targeted AAV-mediated gene delivery has been associated with induction of tolerance toward encoded transgene products, 29 and more recently similar observations have been made in skeletal muscle, a relatively more immunogenic tissue, albeit only at higher levels of transgene expression. 30 Vector delivery to the brain results in either nonresponsiveness or immunity with vector location relative to the blood-brain barrier influencing the response. 31 Collectively these observations suggest that with increased knowledge it is likely to be possible to develop rAAV delivery strategies that favor immune nonresponsiveness and or tolerance to transgene products.…”
Section: Vector Immunobiologymentioning
confidence: 99%
“…Direct intramuscular injection of AAV has been shown to be a convenient, safe, and potentially effective approach for FIX gene transfer. [13][14][15] Intramuscular injection of AAV does not cause severe cellular immune response such as cytotoxic T lymphocyte response in rodent, canine, or human patients. Such severe immune responses were, however, substantial after gene transfers using recombinant adenoviral vector.…”
Section: Introductionmentioning
confidence: 99%
“…16 Formation of inhibitory anti-FIX antibodies, which is the major complication in FIX replacement to treat hemophilia B, has also been observed in preclinical studies of intramuscular AAV gene transfer. 13,[17][18][19] Efficient induction of immune tolerance to FIX is critical for the success of hemophilia treatment. Many factors have been proposed to contribute to induction of immune tolerance or immunity to FIX after muscular AAV gene transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation